Formação da identidade negra: uma análise da obra infantil o cabelo de Lelê. - Lima, Karolainy Vieira (Universidade Federal do Tocantins, 2023)
This work aims to analyze the children's work O Cabelo de Lelê, dealing with the contributions of children's literature, making notes on afrodescendant children's literature and emphasizing, mainly, how the formation of the identity of black children occurs, including issues of acceptance , appropriation of culture and racial identity. According to the contents of the children's book mentioned above, which brings the story of a black girl who is not satisfied with herself and in agreement with authors like Cavalleiro (2001), Coelho (1991), Gomes (2005,2003) and others, who deal with literature, identity issues and racial, the analysis and discussions on such themes are carried out in the four secions present in this work. It is possible to perceive, based on the analysis, that children's works corroborate children's development and identity formation, and that works with Afrodescendant characters contribute to black children in this training process, whereas they identify themselves and feel represented. Even so, it is also notable that they face dwifficulties in appropriating their racial and cultural heritage, since there is a lack of works.